Analisis Tingkat Pemahaman Terhadap Mata Pelajaran Agama Islam Pada Siswa SMP Muhammadiyah 57 Medan - Rambe, Nadiatul Ulyah; Muthi'ah, Siti; Syahril, Muhammad (Yayasan Rahmat Islamiyah, 2024)
If the emotional, cognitive and psychomotor domains are integrated, it can be said that students' understanding of Islamic religious material is good. This will not happen if there is no communication between teachers and students. This does not rule out the possibility that there is no standard assessment carried out by educators in these three fields. To check the reality on the ground, researchers surveyed the research location at SMP Muhammadiyah 57 Medan. This research is field research using qualitative methods. Data was collected through observation, tests and interviews. Data from cases were analyzed descriptively. The findings showed that students were rated very well in the emotional domain based on the observation rubric. For the cognitive domain, only the percentage showed 55% (13 out of 25 students) who were proficient and answered all the questions. Remembering that for the psychomotor cortex, the test is carried out by practicing explaining verses from the Koran and writing verses from the Koran. 14 of the 25 students scored between 91 and 100 points. This means that students are able to express understanding of the material. The obstacles faced by students are the inability to understand the content and the lack of diversity in the student classroom atmosphere.